Learning, Imitation, and the Use of Knowledge: A Comparison of Markets, Hierarchies, and Teams - Butler, John C.; Grahovac, Jovan (Organization Science, 2012)
We use computer simulation to study how different allocations of decision rights give rise to different organizational abilities to maintain and act upon accurate maps of a changing environment. We compare the performance of three archetypal organizational forms as we vary the dynamism and complexity of the environment and the rates at which individuals can observe the environment and imitate each other. We find that teams in which actions are based on plurality votes excel when the task is relatively easy—that is, the ability of individual members to observe the environment is high compared to the environment's dynamism and size. Markets in which all agents act independently perform well when the task is difficult and the agents can easily imitate each other. Hierarchies in which agents in the upper echelons impose actions on their subordinates outperform the other two forms when the agents' abilities to observe the environment are heterogeneous, the task is difficult, and imitation among the agents is moderate. The analysis has implications for the relationship between centralization and the notions of exploitation and exploration in March's influential work [March JG (1991) Exploration and exploitation in organizational learning. Organ. Sci. 2(1):71–87].